Parenting practices among teenage mothers in the city of Duitama, Colombia. - González Bossa, Alieth Rocío; Estupiñán Aponte, María Rosa (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To analyze parenting practices in teenage mothers of Duitama. Methodology. A qualitative assessment with comprehensive focus between February and October 2009 was conducted. It involved mothers aged between 13 and 19 years old chosen from the Municipality Education Secretariat databases, first sampled by logical criteria and then by a snowball. Emerging data from the in-depth interviews and participant observation which were subjected to a qualitative analysis, interpret feeding practices, hygiene, rest, discipline, values and support networks. Results. Executed by verbalization, penalties and prohibitions to instill respect and love values, teenage mothers represent the main figure of authority. They incorporate stimulating environments and games as a strategy for the formation of eating and rest habits. Due to permanent fears personal hygiene is initially delegated to the maternal grandmother as a knowledge provider source, emotional and affective support are considered essential to play the moternal role which also is strengthen by health entities, especially during the breast feeding period. Conclusion. Teenage mothers reproduce cultural patterns which are manifested in the intervention of the other caregivers, specially the teenager’s mother; they have a great impact on daily practices.